2019
DOI: 10.1016/j.orgel.2018.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced effects in organic thin film transistors based on dinaphtho [2,3-b:2′,3′-f] Thieno[3,2-b′] thiophene (DNTT)

Abstract: We have investigated the photoresponse of organic thin film transistors (OTFTs) based on evaporated films of dinaphtho [2,3-b:2',3'-f] thieno[3,2-b'] thiophene (DNNT) as the active semiconductor and spin-coated polystyrene as the gate insulator. Both during illumination and in subsequent measurements in the dark after long periods under illumination, transfer characteristics shift to more positive gate voltages. The greatest photoresponse was achieved at 460 nm, near the absorption maximum of DNTT. The maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Figure c shows the output curves acquired during illumination with different light colors at V GS = −3.6 V. As shown in Figure c, the devices present significantly higher photoswitching properties under blue light illumination ( I DS is almost two magnitude orders higher than I dark ). Following the present results, previous studies have demonstrated that DNTT OFETs exhibit larger photoresponsivities to blue light. ,,, This effect is explained by the fact that OSCs absorb light with a specific wavelength depending on their conjugated bonds and band gap. , For DNTT, phonons with a wavelength of around 450 nm have enough energy to promote exciton formation (electron–hole pairs), which dissociate into holes and electrons during interactions with defects or electric fields. ,, A detailed study of this light-dependent effect was presented by Milvich et al, who showed a strong and slow positive V th shift for DNTT-based transistors under proper biasing and blue light illumination . This photoresponse was explained by a charge trapping mechanism, i.e., the increase in photo-generated electrons and simultaneous trapping of these free charge carriers at structural or interfacial defects.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Figure c shows the output curves acquired during illumination with different light colors at V GS = −3.6 V. As shown in Figure c, the devices present significantly higher photoswitching properties under blue light illumination ( I DS is almost two magnitude orders higher than I dark ). Following the present results, previous studies have demonstrated that DNTT OFETs exhibit larger photoresponsivities to blue light. ,,, This effect is explained by the fact that OSCs absorb light with a specific wavelength depending on their conjugated bonds and band gap. , For DNTT, phonons with a wavelength of around 450 nm have enough energy to promote exciton formation (electron–hole pairs), which dissociate into holes and electrons during interactions with defects or electric fields. ,, A detailed study of this light-dependent effect was presented by Milvich et al, who showed a strong and slow positive V th shift for DNTT-based transistors under proper biasing and blue light illumination . This photoresponse was explained by a charge trapping mechanism, i.e., the increase in photo-generated electrons and simultaneous trapping of these free charge carriers at structural or interfacial defects.…”
Section: Resultssupporting
confidence: 77%
“…17,58 For DNTT, phonons with a wavelength of around 450 nm have enough energy to promote exciton formation (electron−hole pairs), which dissociate into holes and electrons during interactions with defects or electric fields. 9,58,59 A detailed study of this light-dependent effect was presented by Milvich et al, who showed a strong and slow positive V th shift for DNTTbased transistors under proper biasing and blue light illumination. 14 This photoresponse was explained by a charge trapping mechanism, i.e., the increase in photo-generated electrons and simultaneous trapping of these free charge carriers at structural or interfacial defects.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For as-prepared OFETs, onset voltage (Von) is positively shifted from -4 V to 10 V, and the maximum Ids, referring the Ids at Vgs = -60 V, is increased twice in magnitude under light illumination (Fig. 3a), which is a sign of photoconductivity 27 . To quantitatively evaluate photoconductivity, the shift of onset voltage (∆Von) and Iphoto/Idark ratio will be discussed.…”
Section: Resultsmentioning
confidence: 96%
“…Photocurrent in organic semiconductors has been related by several authors to an increase of trapping of minority carriers induced by light exposure 8,[54][55][56][57] . The measurements reported in this work for the OPTs are consistent with this interpretation.…”
Section: Kinetic Modelmentioning
confidence: 99%